Implementation of the Principle of Equality Before the Law in the Dynamics of Indonesian Law - Salomo Jitmau; Naim, Sokhib; Muh Akhdharisa SJ (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the principle of equality before the law in Indonesian positive law and how this principle is understood and applied in practice. The research method used is normative legal research with a sociological jurisprudence approach to describe the gap between law in books and law in action. Data sources were obtained through document studies, including books, journals, and relevant laws and regulations, with qualitative analysis of the deductive model. Novelty of this research is in the form of a legal perspective in understanding and evaluating the implementation of the principle of equality before the law in Indonesia. The results of the study show that the principle of equality before the law has been guaranteed in Article 27 paragraph (1) and Article 28D paragraph (1) of the 1945 Constitution, as well as in a number of other legal regulations such as the Criminal Code (KUHP) and Law Number 48 of 2009 concerning Judicial Power. However, in practice, the implementation of this principle still faces various challenges, including discrimination, abuse of power, and inequality in law enforcement. This study also found a gap between written regulations and implementation in the field, resulting in legal injustice against certain groups. In conclusion, although the principle of equality before the law has become an integral part of the Indonesian legal system, its implementation is still far from ideal. Improvements are needed in the legislative system, law enforcement oversight, and increased public awareness to achieve equal justice under the law. This study provides recommendations for the government and law enforcement officials to be more consistent in implementing the principle of equality before the law, taking into account the moral values of Pancasila as the philosophical foundation of the state.